Students’ Perceptions of Canva and English Learning Motivation: Evidence from Indonesian Senior High School - Dimas Saputra; Martriwati Martriwati (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study investigates senior high school students’ perceptions of Canva as an interactive digital learning tool and its relationship with their motivation to learn English. Although previous studies have reported the educational benefits of Canva, limited research has specifically examined how students’ perceptions of Canva relate to their English learning motivation among senior high school EFL learners. Employing a quantitative descriptive-correlational design, the study involved 204 students who had experience using Canva in English learning activities. The study is grounded in the Technology Acceptance Model (TAM), which explains how users’ perceptions of a technology influence their acceptance and use of digital learning tools. Data were collected through structured questionnaires adapted from the Technology Acceptance Model (TAM) and the Motivated Strategies for Learning Questionnaire (MSLQ). The data were analyzed using descriptive statistics, Pearson correlation, and simple linear regression. The findings revealed that students generally held positive perceptions of Canva, particularly in terms of its usefulness, ease of use, and engagement. The correlation analysis showed a strong positive relationship between students’ perceptions of Canva and their English learning motivation (r = 0.677, p < .001). Furthermore, the regression analysis indicated that students’ perceptions of Canva significantly predicted their motivation, explaining 45.8% of the variance (R² = 0.458). These findings suggest that Canva can serve as a meaningful digital learning medium for enhancing students’ motivation in English learning. The study also extends the application of the TAM by demonstrating that students’ positive perceptions of Canva are associated with higher English learning encourage teachers to integrate interactive digital tools such as Canva into classroom activities to create more engaging, creative and student-centered learning experience.